2016
DOI: 10.1080/21691401.2016.1202257
|View full text |Cite
|
Sign up to set email alerts
|

Novel imatinib-loaded silver nanoparticles for enhanced apoptosis of human breast cancer MCF-7 cells

Abstract: In the current study, in vitro biological feature of imatinib-loaded silver nanoparticles (IMAB-AgNPs) on human breast cancer cell line was investigated. The formation of synthesized silver nanoparticles (AgNPs) was characterized by UV-Visible spectroscopy, EDS, TEM imaging, SEM, FTIR, DLS and Zeta potentiometer. The developed IMAB-AgNPs with maximum percentage of loading efficiency was demonstrated in the average of 130 nm and mostly spherical. Additionally, in vitro drug release study showed a slow and conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 28 publications
(27 reference statements)
2
33
0
Order By: Relevance
“…Our previous work showed that Tap73/DNp73 plays an important role in regulating apoptosis via mitochondrial pathway [29,30]. Apoptosis is regulated by pro-apoptotic and antiapoptotic effectors that involve a different pathway, such as Bcl-2 and caspase pathways which serve as important regulators of apoptosis pathways [42]. In our previous work, the magnitude of radiation effects in mouse testis evoked by carbon ion irradiation was marked by morphology changes, significant rise in apoptotic cells, up-regulation the ratio of pro-apoptotic Tap73/anti-apoptotic DNp73, as well as alterations of crucial mediator of the mitochondrial pathway [29].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work showed that Tap73/DNp73 plays an important role in regulating apoptosis via mitochondrial pathway [29,30]. Apoptosis is regulated by pro-apoptotic and antiapoptotic effectors that involve a different pathway, such as Bcl-2 and caspase pathways which serve as important regulators of apoptosis pathways [42]. In our previous work, the magnitude of radiation effects in mouse testis evoked by carbon ion irradiation was marked by morphology changes, significant rise in apoptotic cells, up-regulation the ratio of pro-apoptotic Tap73/anti-apoptotic DNp73, as well as alterations of crucial mediator of the mitochondrial pathway [29].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis induction in E. coli-infected macrophages by pure and encapsulated HHC10 peptide was evaluated by Annexin V-PI method using by flow cytometry [29,30]. It was investigated by staining macrophages with FITC-conjugated Annexin V-PI apoptosis kit according to the manufacturer protocol (Sigma).…”
Section: Apoptosis Assaymentioning
confidence: 99%
“…Recent studies have shown that the expression of GSH and subunits of two GSH-synthesizing enzymes along with the associated mRNA expression are downregulated in human liver cells. These responses were accompanied by mitochondrial membrane disruption through the downregulation of Bcl-2 protein expression and concomitant upregulation of Bax protein expression [21,37]. The opening of the mitochondrial membrane is inhibited and stimulated by Bcl-2 and Bax, respectively.…”
Section: Phagocytosis and Ros Generationmentioning
confidence: 99%